Resourcing the start-up business : creating dynamic entrepreneurial learning capabilities - Jones, Oswald; Mcpherson, Allan; Jayawarna, Dilani (New York, NY : Routledge, 2023)
"Drawing on the most up-to-date and relevant research, this concise textbook is an accessible guide to harnessing the appropriate resources when launching a new start-up business. The focus is on the wide range of tangible and intangible resources available to entrepreneurs in the early stages of a new venture. This second edition brings in material on crowdfunding, digitalization and covid-19, and dedicates new chapters to: lean start-ups and business models, idea generation and opportunity development, and business incubators and accelerators. The book supports students with learning objectives, a summary, discussion questions and a practical call to action in each chapter. A teaching guide and slides are also available for instructors. Resourcing the Start-Up Business will be a valuable textbook for students of entrepreneurship and new venture creation globally"--
Revised edition of the authors' Resourcing the start-up business, 2014.
OCLC-licensed vendor bibliographic record.
Keywords: New business enterprises -- Management; Small business -- Management; Business planning; Entrepreneurship; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Entrepreneurship